Freedom Communications, Inc : family enterprise or liquidity? - Ward, John L., 1945- (SAGE Knowledge. Cases., 2007)
The case explains the complex divisions and ownership of Freedom Communications Inc. by the Hoiles family and the different options the family shareholders must explore for liquidating their individual shares of the company.